Post a New Question

Mathematics - Trigonometric Identities

posted by .

Let y represent theta

Prove:

1 + 1/tan^2y = 1/sin^2y



My Answer:

LS:

= 1 + 1/tan^2y
= (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y)
= (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y)
= (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y)
= (sin^2y + cos^2y) + (sin^2y + cos^2y)(sin^2y) / (sin^2y)(cos^2y/sin^2y)

... And now I confuse myself

Where did I go wrong? And please direct me on how to fix it?

  • Mathematics - Trigonometric Identities -

    you confused me too

    I will start again with
    LS = 1 + cot^2 y
    = 1 + cos^2 y/sin^2 y , now find a common denominator
    = (sin^2 y + cos^2 y) / sin^2 y, but sin^2 y + cos^2 y=1
    = 1/sin^2 y
    = RS

  • Mathematics - Trigonometric Identities -

    I'm not suppose to use the inverse identities yet ...

  • Mathematics - Trigonometric Identities -

    ok, then in

    LS = 1 + 1/tan^2y

    = 1 + 1/(sin^2 / cos^2 y)
    = 1 + (cos^2 y)/(sin^2 y)
    = ... my second line

    surely you are going to use tanx = sinx/cosx !!!

    we are not using "inverse identities" here

  • Mathematics - Trigonometric Identities -

    I meant the reciprocals of SOH CAH TOA

    And ... I just got it


    Here's my answer:

    LS:

    = 1 + 1/tan^2y
    = 1 + 1/(sin^2y/cos^2y)
    = 1 + 1(cos^2y/sin^2y)
    = 1 + cos^2y / sin^2y
    = 1 + 1-sin^2y / sin^2y
    = 1(sin^2y) / sin^2y + 1 - sin^2y / sin^2y
    = sin^2y + 1 - sin^2y / sin^2y
    = 1/sin^2y

  • Mathematics - Trigonometric Identities -

    yes
    correct

  • Mathematics - Trigonometric Identities -

    should have taken a closer look at your solution.
    the last few lines make no sense with "no brackets" being used

    why don't you follow the steps of my original solution, it is so straightforward.

  • Mathematics - Trigonometric Identities -

    cscx-cotx forms an identity with?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trig

    Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < 2pi Find: sin (v + u) cos (v - u) tan (v + u) First compute or list the cosine and sine of both u and v. Then use the combination rules sin (v + u) = sin u cos …
  2. algebra

    Can someone please help me do this problem?
  3. Trigonometry

    Please review and tell me if i did something wrong. Find the following functions correct to five decimal places: a. sin 22degrees 43' b. cos 44degrees 56' c. sin 49degrees 17' d. tan 11degrees 37' e. sin 79degrees 23'30' f. cot 19degrees …
  4. Trigonometry

    1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two decimal places. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that …
  5. Trig Identities

    Proving identities: 1) 1+ 1/tan^2x = 1/sin^2x 2) 2sin^2 x-1 = sin^2x - cos^2x 3) 1/cosx - cosx = sin x tan x 4) sin x + tan x =tan x (1+cos x) 5) 1/1-sin^2x= 1+tan^2 x How in the world do I prove this...please help... I appreciateyour …
  6. precalculus

    For each of the following determine whether or not it is an identity and prove your result. a. cos(x)sec(x)-sin^2(x)=cos^2(x) b. tan(x+(pi/4))= (tan(x)+1)/(1-tan(x)) c. (cos(x+y))/(cos(x-y))= (1-tan(x)tan(y))/(1+tan(x)tan(y)) d. (tan(x)+sin(x))/(1+cos(x))=tan(x) …
  7. Trigonometry desperate help, clueless girl here

    2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) …
  8. MathsSs triG

    Consider sin(x-360)sin(90-x)tan(-x)/cos(90+x) 1.A.SIMPLIFY sin(x-360)sin(90-x)tan(-x)/cos(90+x) to a single trigonometric ratio B.hence or otherwise without using a calculator,solve for X if 0<X<360. sin(x-360)sin(90-x)tan(-x)/cos(90+x) …
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions

Post a New Question